Prunus quanzhouensis: a newly discovered species of Prunus subgen. Cerasus (Rosaceae) from northeastern Guangxi, China - Liang, Sheng-Hua; Qin, Bo; Huang, Yao-Heng; Tang, Li-Ming; Zhang, Zhan-Jiang; Li, Cui; He, Ying-Hui; Jiang, Ri-Hong; Li, Jian-Ling (Phytotaxa, 2023)
Prunus quanzhouensis is a new species of Rosaceae discovered in Guangxi, China, which is here described and illustrated. Despite its morphological similarities to P. campanulata, P. conradinae and P. xueluoensis, it can be distinguished from them by being shrubs or small trees, with 1.5–3.0 m tall, leaves with 10–13 pairs of lateral veins, abaxially glabrous involucral bracts, adaxially appressed villous bracts, flowers measuring 1–1.2 cm in diameter, tubular hypanthium with about 9×3 mm, oblique sepals, 30–35 stamens, and a style that is villous and longer than the stamens. Less than six populations of this new species have been found in the type locality, with approximately 130 mature individuals, which accounted for more than 95% of the total population. Based on direct observation in the field and the IUCN Red List Categories and Criteria, P. quanzhouensis is classified as Endangered (EN).